PELATIHAN PENGOLAHAN LIMBAH DAPUR MAKAN BERGIZI GRATIS (MBG) MENJADI EKOENZIM DAN PUPUK KOMPOS - Muanah Muanah; Ida Wahyuni; Ahmad Fatoni; Marianah Marianah; Basirun Basirun (Universitas Muhammadiyah Mataram, 2026)
The problem of free nutritious kitchen waste is an environmental issue that requires proper, effective, and efficient handling. The types of waste produced also vary, such as vegetable scraps, various fruit peels, and leftovers. The purpose of the mentoring is to improve the knowledge and skills of millennial farmer groups to process kitchen waste into products of economic value. There are three mentoring methods, namely counseling, training, and activity evaluation. The target partners who were mentored during the activity were members of the millennial farmer cadet group and the general public in Batu Putik Village. To find out the level of understanding of the participants, the team prepared a questionnaire to be filled out by the participants before and after the activity, the results of the mentoring showed that the participants who actively participated in the activity until the end were 17 out of 26 people who were mentored. Of the 17 participants who were considered active, it showed that before the activity the knowledge they had reached 17% while after the mentoring it increased significantly to 87%, as well as the skills in processing MBG kitchen waste into products of economic value such as ecoenzymes and compost previously with skills below 10% but after mentoring it became 78%.